Measurement bias in self-reports of offending: a systematic review of experiments - Gomes, Hugo S. (Journal of experimental criminology, 2019)
Self-reported offending is one of the primary measurement methods in criminology. In this article, we aimed to systematically review the experimental evidence regarding measurement bias in self-reports of offending.